The degree, extent and value of air temperature amelioration by urban green spaces in Bulawayo, Zimbabwe. Issue 3 (1st September 2020) - Ngulani, T.; Shackleton, C.M.
ABSTRACT: Urban greenery provide a variety of goods and services to city dwellers. A core one is amelioration of the urban heat island effect. However, the many estimates from temperate regions cannot be extrapolated to the tropics, where more empirical studies are required to guide urban planning and optimization of green infrastructure design and distribution. This study reports on the temperature differentials in fortnightly readings, in winter and summer, between 12 urban green spaces and the surrounding built-up urban matrix at increasing distances from each green space. Additionally, the value of energy costs saved for air conditioning by urban greenery was calculated. The mean difference in temperature between green spaces and neighbouring built-up areas was 3.6°C, and in summer ranged from 0.9°C to 6.1°C and in winter 0.9°C to 5.7°C. The cooling effects extended up to 1.7 km beyond the centre of green spaces. The magnitude of cooling increased slightly with increasing green space size. These cooling effects translated into a cost on energy saving of approximately US532/household/yr. Given the weak economy and incomes in Zimbabwe, this saving is considerable and can contribute to the multiple motivations for more green spaces in the city.